2022
DOI: 10.15562/bmj.v11i1.3158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of maternal death with COVID-19 in rural tertiary care center: A retrospective-descriptive Study

Abstract: Background: Maternal with to COVID-19 is a new maternal emergency issue leading to maternal morbidity and mortality. In Indonesia, the number of cases of maternal mortality with COVID-19 began to increase. This study aims to determine the characteristic of maternal deaths due to COVID-19 in a tertiary care center in Indonesia.Method: This observational-retrospective study descriptively analyzed 15 maternal deaths due to COVID-19 admitted to the Department of Obstetrics and Gynaecology at the tertiary care teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There was one article that mentioned the increased risk of intubation and severe pneumonia (D'Antonio et al, 2021) Three studies mentioned the comorbidities found in patients. Almost all of the pregnant women aged >35 years had comorbidity (Djusad et al, 2021;Kurniawati et al, 2022;Shams et al, 2022). The most common comorbidity found was obesity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was one article that mentioned the increased risk of intubation and severe pneumonia (D'Antonio et al, 2021) Three studies mentioned the comorbidities found in patients. Almost all of the pregnant women aged >35 years had comorbidity (Djusad et al, 2021;Kurniawati et al, 2022;Shams et al, 2022). The most common comorbidity found was obesity.…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in mortality in the AMA group compared with the non-AMA group. Two studies found that almost all maternal death in advanced-age mothers were complicated by preeclampsia (Djusad et al, 2021;Kurniawati et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations